If $f: R \rightarrow R$ be given by $f(x)=\left(3-x^{3}\right)^{\frac{1}{3}},$ then $fof(x)$ is ..........
$f : R \rightarrow R$ be given as $f ( x )=\left(3-x^{3}\right)^{\frac{1}{3}}$
$\therefore fof ( x )= f ( f ( x ))=f\left(3-x^{3}\right)^{\frac{1}{3}}$ $=\left[3-\left(\left(3-x^{3}\right)^{\frac{1}{3}}\right)^{3}\right]^{\frac{1}{3}}$
$=\left[3-\left(3-x^{3}\right)\right]^{\frac{1}{3}}=\left(x^{3}\right)^{\frac{1}{3}}$
$\therefore fof(x)=x$
The correct answer is $D$.
Consider $f:\{1,2,3\} \rightarrow\{a, b, c\}$ given by $f(1)=a, \,f(2)=b$ and $f(3)=c .$ Find $f^{-1}$ and show that $\left(f^{-1}\right)^{-1}=f$.
Let $f:\left[ {4,\infty } \right) \to \left[ {1,\infty } \right)$ be a function defined by $f\left( x \right) = {5^{x\left( {x - 4} \right)}}$ then $f^{-1}(x)$ is
If $f(x) = 3x - 5$, then ${f^{ - 1}}(x)$
Let $S=\{a, b, c\}$ and $T=\{1,2,3\} .$ Find $F^{-1}$ of the following functions $F$ from $S$ to $T$. if it exists. $F =\{( a , 2)\,,(b , 1),\,( c , 1)\}$
The inverse of $y=5^{\log x}$ is